The Influence of Hedonic Shopping Value and Sales Promotion on Impulse Buying Through Urge to Buy Impulsively as a Mediating Variable - Fitriani, Nur Afika; Sudarmiatin; Winarno, Agung (Universitas Muhammadiyah Pontianak, 2026)
This study examines the influence of hedonic shopping value and sales promotion on impulse buying through urge to buy impulsively among Shopee Live Streaming users in Malang City. Using a quantitative approach, data were collected from 385 respondents through questionnaires and analyzed using SEM-PLS with SmartPLS 4.0. The results show that hedonic shopping value significantly affects impulse buying and urge to buy impulsively, while sales promotion only significantly affects urge to buy impulsively. Urge to buy impulsively significantly mediates impulse buying behavior. The findings highlight the importance of emotional and psychological factors in live-streaming e-commerce. Keywords: Hedonic Shopping Value; Sales Promotion; Urge to Buy Impulsively; Impulse Buying; Shopee Live Streaming